AUTHENTIC ASSESSMENT IN MUSIC LEARNING - Irwan; Yusnelli; Nofridayati; Iswandi; Nursyirwan; Delfi Enida (Indonesian Journal of Education (INJOE), 2023)
The purpose of this study is to analyze and know how and what is related to the title of Authentic Assessment in Music Learning. This research method This form of research is qualitative with descriptive and critical analysis. Therefore, the author can elaborate comprehensively how Authentic Assessment In Music Learning. In this study, the author optimally used two data sources related to this study, namely. Primary data sources and secondary data sources. The main sources of this research are books and scientific journals on Authentic Assessment. The result of this study is that practical music education is an innovative method that needs to be further developed, considering the practical aspects that characterize art education in schools. As they create their pieces, students develop their musical skills and creativity, allowing them to collaborate in groups to create unique pieces of music. This "musical" music learning seems to be an answer to the tendency of music learning that is theoretical and linguistic that only prioritizes cognitive aspects.